Photo-induced ferroelectric switching in perovskite CH3NH3PbI3 films. Issue 11 (6th February 2017) - Wang, Peiqi; Zhao, Jinjin; Wei, Liyu; Zhu, Qingfeng; Xie, Shuhong; Liu, Jinxi; Meng, Xiangjian; Li, Jiangyu
Abstract : Strong interactions between polarization and light are demonstrated in CH3 NH3 PbI3 films with good photovoltaic conversion efficiencies. Abstract : The photovoltaic conversion efficiency of perovskite solar cells based on organic–inorganic CH3 NH3 PbI3 has risen spectacularly from 3.8% to over 20% in just seven years, yet quite a few important fundamental issues have not been settled, and the role of spontaneous polarization remains poorly understood. While piezoresponse force microscopy (PFM) has been adopted to probe possible ferroelectricity in CH3 NH3 PbI3, the reported data are often conflicting and inconclusive, due to the complexity in the apparent piezoresponse and its switching that may arise from ionic motions, electrostatic interactions, and other electromechanical mechanisms. Here, using a combination of microscopic and macroscopic measurements, we unambiguously establish the linear piezoelectricity of CH3 NH3 PbI3 arising from its spontaneous polarization, which can be switched by an electric field, though other electromechanical contributions such as ionic motions are also shown to exist. More importantly, we demonstrate strong interactions between polarization and light in technologically relevant CH3 NH3 PbI3 films with good conversion efficiencies, observing that the spontaneous polarization can also be switched by light illumination in the absence of an electric field. The light is shown to reduce the coercive voltage of CH3 NH3 PbI3 and shifts its nucleation bias, suggesting that the photo-induced switching is caused by ionic motions in combination with a photovoltaic field. This set of studies offer strong evidence on the interactions among photo-induced charges, polarization, and ions in perovskite CH3 NH3 PbI3, and these fundamental observations lay the ground for answering the technologically important question regarding the effects of ferroelectricity on its photovoltaic conversion.